PENGUJIAN FILTER PARTIKULAT ASAP ROKOK ELECTROSTATIC PRECIPITATOR DENGAN ELEKTRODA TEMBAGA DAN ALUMUNIUM - Anggraini, Ika Novia (UNIB Press, 2023)
Cigarette smoke is a source of air pollution, especially indoors. The smoke from burning cigarettes doesn't just evaporate into the air, but there is nicotine residue that sticks to the dust or items around the smoker, such as clothes, carpets, walls. A smoke filter or smoke particulate filter is something that is really needed to reduce pollutants in the room. Research on